CORRELATION OF THE USE DURATION OF DEPOPROGESTIN INJECTION WITH THE INCREASE OF BODY WEIGHT AT DULUMAI VILLAGE HEALTH CENTER PAMONA PUSELEMBA SUBDISTRICT, POSO REGENCY - Rosalina Wayan (Stikes Graha Edukasi Makassar, 2019)
Introduction: The modern contraception method, which is effective and non-permanent, is the progestine depot and one of the injection method given in 3-month interval (12 weeks), which is very effective, safe able to use by all women at reproductive ages to return their late fertilizations of about 4 months and suitable for lactation period since it does not suppress breast milk production. The progestine depo though fulfills the requirement to become the ideal contraception, it also has shortcoming, such as the disturbing the menstruation pattern, it also delays the recovery of the fertilization and the increase of the body weight. Method: The research uses the approach of Cross sectional Study, with the total population of 808 people and 267 samples. The secondary data were collected using the check list sheets, and the data processing used the computerization program and the data were analyzed using Chi-square test. Result: Indicated that there is no significant correlation between the use duration of depoprogestine contraception and the increase of body weight at Dulumai Village Health Center, Pamona Puselemba Sub-District, Poso Regency. Conlusion: The midwives and other health officers can give counceling about the limitation of depoprogestine contraception so that there is the acceptors do not have worries any more about the use of that contraception; one of them is the increase of the body weight.